Retiform Hemangioendothelioma of the Neck - Kuo, Chin-Lung; Chen, Paul Chih-Hsueh; Li, Wing-Yin; Chu, Pen-Yuan (Journal of pathology and translational medicine, 2015)
After discussion with the head and neck oncology multidisciplinary team, a regular follow-up program was scheduled for the patient without postoperative radiation or chemotherapy, because of the clear surgical margins and rare mitosis observed, and to avoid the potential life-long complications associated with radiation therapy. DISCUSSION To date, only 32 cases of RH have been reported in the English literature.4 The etiology of this disease remains unclear; although cases related to previous epidermal malignant neoplasms, radiotherapy, human herpes virus type 8 and lymphedema have been reported, the exact associations have not been clearly established.2,4,5 Disease duration from the time of diagnosis ranges from 2 months to several years.2,3,6 Most patients present between the second to fourth decades of life (mean age, 36 years).2 There is a female predominance, with a female-to-male ratio of 2:1.2,3,6 RH can develop as either exophytic or plaque-like lesions with size ranging from 1 to 30 cm.3,6 Most cases appear in the extremities, with a higher incidence in the lower limbs. [...]RH is considered to be a vascular tumor, while Dabska-RHs have a lymphatic endothelial phenotype.8 Cytologic or pathological examination reports may provide surgeons with appropriate guidelines for the treatment of patients, and the most compelling evidence in the differential diagnosis of RH is provided by immunohistochemistry, in which tumor cells react with endothelial markers (e.g., CD31, Fli-1, and factor VIII-related antigen).2,5,9,10 CD31 is generally regarded as the single best marker of endothelial cell differentiation because it is expressed in 90% of endothelial cell tumors, but very rarely in carcinomas, lymphomas, and mesotheliomas.9 Factor VIII-related antigen has low sensitivity, and frequent presence of significant "background" due to staining of circulating antigen greatly limits the use of this marker.10 Hence, the expression of this marker was not determined in this patient.